URGENSI TRANSPARANSI TAHAPAN PEMUTAKHIRAN DATA PEMILIH DAN PENYUSUNAN DAFTAR PEMILIH PADA PEMILIHAN UMUM TAHUN 2024 DI KOMISI PEMILIHAN UMUM KOTA PALEMBANG - Jannah, Miftahul; Nofrima, Sanny; Putra, Dwiki Adi (JURNAL ILMIAH EDUNOMIKA, 2025)
The main objective of this research is to determine the level of urgency of transparency implemented by the Palembang City KPU in the process of updating voter data and compiling voter data in the 2024 elections. In this thesis the researcher uses qualitative methods, by obtaining data through interview, observation and documentation techniques. The results of this research show that using transparency theory according to Asmoro which includes 4 indicators, namely financial condition, institutional management, operational performance and institutional ownership. In this case, it was found that the Palembang City KPU did not routinely publish financial reports related to updating voter data, due to obstacles such as regional voter borders, the formation of polling station boundaries and a very large budget which could hamper the holding of the election. The transparency that has been carried out by the Palembang City KPU in the process of updating voter data and compiling the voter list can reduce the risk of incidents occurring in the process. By ensuring that all stages are carried out openly and can be published by the public, it will be difficult for irresponsible parties to manipulate data or processes. By carrying out the process openly, the public can monitor and ensure the integrity of all stages of the election. This can build public confidence that elections will take place fairly and democratically, as well as prevent discrimination against citizens who meet the requirements but have difficulty registering.